ANALISIS PENURUNAN SISTEM KOMPRESOR PADA PEMBANGKIT PT. INDOCEMENT TUNGGAL PRAKARSA, TBK. KALIMANTAN SELATAN - Firmansyah, Ilham Arif; Mursadin, Aqli (Universitas Lambung Mangkurat, 2021)
Supply of compressed air has an important role in continuity of operation power plant, failures that occur in operation of engine in this unit can affect all plant operations that can result in decreased production levels. To determine the magnitude of loss of pressure or energy loss lost in pressurized air piping system at plant located in PT. Indocement Tunggal Prakarsa, Tbk. Tarjun Plant-12. Evaluation of pressure reduction losses in the air system is focused on losses caused by system leakage and pressure drops in the distribution lines caused by several factors including friction in straight pipes, bends, fittings, reducers and existing components, and knowing the loss of costs due to compressor pressure drop. The pressure drop in the pipe is very dependent on pipe diameter, besides distance and supporting components on piping system also affect the pressure drop. Based on calculation, there was a decrease in pressure of 1603660,895 Pa, from pressure drop caused by friction of straight pipe and connection and actual condition of pipe surface which was likely to have been corroded, making surface rough. system decline that occurred in the compressor resulted in a loss of operational costs of 5,760,451 rupiah / week.